2019
DOI: 10.28998/rca.v17i2.7432
|View full text |Cite
|
Sign up to set email alerts
|

Variedades E Formas De Adubação No Cultivo De Soja E Milho Em Consórcio

Abstract: A consorciação entre culturas permite maior aproveitamento da área cultivada. Nesta pesquisa objetivou-se avaliar formas de adubação de semeadura e variedades de soja, em diferentes arranjos espaciais, no consórcio com milho para produção de silagem. Foram realizados dois ensaios: (1) milho no espaçamento de 1m entre fileiras com uma linha de soja na entrelinha; (2) e o milho em fileiras duplas alternadas com uma fileira de soja, em espaçamento único de 0,50 m entre fileiras. O delineamento usado foi o de bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
1
0
3
Order By: Relevance
“…The image monitoring on soybeans showed that the high index values in the lower part of the area may be associated with a less advanced stage of senescence compared to the treatments located in the upper block, or also possibly due to the greater soil moisture in the areas located in the lower areas of the plot, providing greater plant vigor (Figure 6). On the other hand, the high values for the coffee crop throughout the area may be associated with the fact that soybeans provided a great advantage in terms of biological nitrogen fixation, making a significant contribution to plant vigor [41,42]. The low variability of the index values for the coffee crop also indicates that the soybean intercropping did not result in morphophysiological changes in the coffee plant.…”
Section: Discussionmentioning
confidence: 99%
“…The image monitoring on soybeans showed that the high index values in the lower part of the area may be associated with a less advanced stage of senescence compared to the treatments located in the upper block, or also possibly due to the greater soil moisture in the areas located in the lower areas of the plot, providing greater plant vigor (Figure 6). On the other hand, the high values for the coffee crop throughout the area may be associated with the fact that soybeans provided a great advantage in terms of biological nitrogen fixation, making a significant contribution to plant vigor [41,42]. The low variability of the index values for the coffee crop also indicates that the soybean intercropping did not result in morphophysiological changes in the coffee plant.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2021) conduziram consórcio de milho com espaçamento de um metro entre fileiras e seis plantas m linear⁻¹ (60 mil plantas ha⁻¹) com uma linha de soja conduzida na entrelinha do milho, com 25 plantas m linear⁻¹ (250 mil plantas ha⁻¹), onde observaram-se prejuízos de produtividade no consórcio milho e soja (IEA<1,0) Cardoso et al (2019). …”
unclassified
“…diferença estatística das médias em todas estas variáveis Corrêa et al (2011),. por sua vez, no uso do consórcio na mesma linha de semeadura, semelhante ao modelo implantado no presente trabalho, não observaram efeito na produção de milho para silagem ou grão em sistema orgânico Cardoso et al (2019). e Oliveira et al (2021) não observaram incremento em produtividade de MS em consórcio entre milho e soja.…”
unclassified
See 1 more Smart Citation